Access to Highly Substituted Pyrimidine N-Oxides and 4-Acetoxymethyl-Substituted Pyrimidines via the LANCA Three-Component Reaction–Cyclocondensation Sequence - Schefzig, Luise; Kurzawa, Timon; Rancan, Giaime; Linder, Igor; Leisering, Stefan; Bera, Mrinal K.; Gart, Max; Zimmer, Reinhold; Reissig, Hans-Ulrich (Synthesis, 2021)
The LANCA three-component reaction of lithiated alkoxyallenes (LA), nitriles (N), and carboxylic acids (CA) smoothly provides β-alkoxy-β-ketoenamides in broad structural variety. The subsequent cyclocondensation of these compounds with hydroxylamine hydrochloride afforded a large library of pyrimidine N-oxides under mild conditions and in good yields. Their synthetic utility was further increased by the Boekelheide rearrangement leading to 4-acetoxymethyl-substituted pyrimidines. With trifluoroacetic anhydride the rearrangement proceeds even at room temperature and directly furnishes 4-hydroxymethyl-substituted pyrimidine derivatives. The key reactions are very robust and work well even in the presence of sterically demanding substituents.
Keywords: alkoxyallene; β-alkoxy-β-ketoenamide; pyrimidine N-oxide; Boekelheide rearrangement; oxidation